DAMPAK STRATEGI PEMASARAN DIGITAL TERHADAP LOYALITAS KONSUMEN DI E-COMMERCE: STUDI KASUS SHOPEE INDONESIA - Muhajirin Muhajirin; Ita Purnama; Novi Kadewi Sumbawati (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2025)
This study aims to analyze the impact of digital marketing strategies on consumer loyalty in the Shopee Indonesia e-commerce platform. Digital marketing encompasses various methods such as digital advertising, social media, loyalty programs, and flash sales, which are employed to attract and retain consumers. The study uses a quantitative approach with a survey of 200 respondents who are active Shopee users. The results indicate that digital marketing has a significant influence on consumer loyalty, with loyalty programs having the greatest impact, followed by digital advertising, social media, and flash sales. A simple linear regression analysis shows that digital marketing accounts for 56% of the variation in consumer loyalty. This research highlights the importance of integrated digital marketing strategies to enhance consumer engagement and loyalty.